Comparative evaluation of the morphology and enzyme activities of the digestive system of red jungle fowl, and native village and commercial broiler chickens - Kadhim, Khalid Kamil (2011)
A study was carried out to compare the morphology of the digestive system, as well as the pancreatic and small intestinal enzymatics activities between the Red jungle fowl (RJF) and the native village chicken (NVC). The findings for the two breeds were compared with the commercial broilers (CBC) which had been consciously selected for high body weight. Ten male birds from each breed were serially euthanized at day 1, 10, 20, 56 and 120 post-hatch, respectively. The total body weight, as well as the absolute and relative weights of the digestive organs and the length of the intestinal segments were measured and recorded. Histological examinations of the digestive organs were carried out by light microscopy. The mucosubstances of the salivary glands and mucosa of the digestive tract were evaluated using histochemical methods. Histomorphometric evaluations of the intestinal mucosa, including the villus height, villus surface area and crypt depth, were also performed. In addition, the number of villi for each intestinal segment was counted through cross-sections of the villi obtained by a new method, and the intestinal surface area was also measured. The three-dimensional intestinal mucosa was evaluated using scanning electron microscopy (SEM). The enzymatic activities of amylase, trypsin and chymotrypsin of the pancreas and small intestinal (duodenum, jejunum and ileum) contents were also investigated. At day 10 post-hatch, the body weight of the CBC was higher (P<0.05) than those of the NVC and RJF by approximately 4 and 6 folds, respectively, and these were increased to approximately 5 and 10 folds, respectively at day 20 post-hatch onwards. Nonetheless, the NVC showed a higher (P<0.05) body weight than that of the RJF at approximately by two folds at day 20 post-hatch. The absolute weights and lengths of the digestive organs were dominantly greater (P<0.05) in the CBC followed by the NVC, while the RJF had the least value. However, the results were reversed when the data attributed to the body weight, except for day 1 post-hatch, where the CBC showed the highest value. Grossly, the arrangement of the lingual papillae was in a straight row in the CBC and in a concave row in both the NVC and RJF, whereas, the pharyngeal papillae were double rows in the CBC, with a second rudimentary row in NVC and restricted to only a single row in the RJF. The shapes of the liver lobes in the RJF and NVC were more consistent with domestic chicken than CBC. As for the blood supply of the viscera, the numbers of the jejunal and ileal branches were found to be higher in the CBC compared to those in the NVC and RJF. Histologically, the digestive system of the three chicken breeds showed many similarities. The proventricular glands are located in between the layers of their muscularis mucosa. The paneth cells and the enterochromaffin cells in the intestinal mucosa were investigated using the light microscopy of a specific staining method.The histochemical observations of the salivary glands and mucosa of the digestive system for the presence of neutral and acid mucin (sulphated and carboxylated) revealed no difference between the breeds. The distribution of neutral and acid mucin was dominantly observed in the upper digestive tract, whereas, the intestinal mucin of the goblet cells contained mostly sulphated and carboxylated mucosubstances. The pancreatic ductal system showed the absence of the ductal glands and the goblet cells. However, the luminal mucin reaction of the epithelial cells lining these ducts was observed in all the three breeds. The histomorphometric evaluations revealed that the thickness of the wall of the digestive organs was different between the three breeds. In absolute bases, the CBC showed dominantly greater values, followed by the NVC, while the RJF showed the least value. On the contrary, the data were reversed on the relative bases. The height and the surface area of the villi, as well as the muscularis externa were significantly higher (P<0.05) in the CBC than those in the NVC and RJF. The number of villi in each intestinal segment was higher (P<0.05) in the NVC and RJF compared to the CBC, and a similar result was also observed for the intestinal surface area, however, the jejunal surface area was higher in the CBC. The SEM examinations revealed that the epithelial cells of the intestinal villi in the CBC have high activities at the early age, as demonstrated by the presence of numerous recesses, cell protuberance, cell clusters, dome-shaped cells, clear cell outlines, cell exfoliated and extrusion area. Whereas, in the NVC and RJF represented by the discontinuity of epithelia and corrugated surface. The characteristic star-shape villi in the mid-cecum region were observed in the three breeds. The absolute and relative pancreatic enzyme activities were higher (P<0.05) in the CBC than those of the NVC and RJF. Similar results were also observed for the absolute enzymatic activity of the intestinal contents. However, the data were shown to be reversed in the relative bases. In conclusion, the difference in the growth rate between the breeds was positively associated with the growth and development of the digestive organs. In the CBC, changes markedly occurred during the early stages of life, whereby the change was observed to be rather biased towards the digestive tube giving the body organization designed for fast growth. During the late stages of development, it was biased towards the pectorals and the feathers. As for the NVC and RJF, it was obviously more valuable to have satisfactory protection against cold and rain at the earliest stage possible, and also some flying power in the young RJF as a protection against their predators. The effects of selection and the genetic variation might affect the growth rate of the digestive organs and the enzyme synthesis according to life cycle requirements, and this could be a limiting factor in the digestion and subsequently the growth rate.